Tectonic evolution of a Paleozoic thrust fault influences the hydrogeology of a fractured rock aquifer, northeastern Appalachian foreland. Issue 3 (19th February 2014) - Kim, J.; Ryan, P.; Klepeis, K.; Gleeson, T.; North, K.; Bean, J.; Davis, L.; Filoon, J.
Abstract In polyorogenic regions, the superposition of structures during a protracted tectonic history produces complex fractured bedrock aquifers. Thrust‐faulted regions, in particular, have complicated permeability patterns that affect groundwater flow paths, quantity, and quality. In the Appalachian foreland of northwestern Vermont, numerous bedrock wells that are spatially related to the Paleozoic Hinesburg thrust have elevated naturally occurring radioactivity and/or low yields. The association of groundwater quality and quantity issues with this thrust was a unique opportunity to investigate its structural and hydrogeologic framework. The Hinesburg thrust juxtaposed metamorphic rocks of the hanging wall with sedimentary rocks of the footwall during the Ordovician. It was then deformed by two orthogonal Devonian fold sets and was fractured during the Cretaceous. Median well yields in the hanging wall aquifer are significantly lower than those of the footwall aquifer, consistent with the respective permeability contrast between metamorphic and carbonate rocks. For wells drilled through the Hinesburg thrust, those completed closest (vertically) to the thrust have the highest median yields, whereas others completed farther below have yields in the footwall range. The geochemical signature of the hanging wall and footwall aquifers correlates with their whole‐rock geochemistry. The hanging wall aquifer is enriched in alpha radiation, Na+K‐Cl, Ba, and Sr, whereas the footwall aquifer is enriched in Ca‐Mg‐HCO3 and alkalinity. Wells that penetrated the Hinesburg thrust generally have hanging wall geochemical signatures. A simple hydrogeologic model for the permeability evolution of the Hinesburg thrust involves the ductile emplacement of a low‐K hanging wall onto a high‐K footwall, with subsequent modification by fractures.